2011
DOI: 10.1155/2011/530926
|View full text |Cite
|
Sign up to set email alerts
|

A Proteome Reference Map of the Causative Agent of Melioidosis Burkholderia pseudomallei

Abstract: Burkholderia pseudomallei is the etiologic agent of melioidosis. Using 2DE and MALDI-TOF MS, we report here a proteome reference map constructed from early stationary phase, a bacterial adaptation process. We identified 282 protein spots representing 220 ORFs; many of them have been implicated in bacterial pathogenesis. Up to 20% of identified ORFs belong to post-translational modification and stress responses. The proteome reference map will support future analysis of the bacterial gene and environmental regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Interestingly, when compared against other prokaryotic transcriptome studies, the transcriptional landscape of Bp Chr 1 bears high resemblance to other single chromosomal microbes E. coli , L. monocytogenes and B. subtilis [4], [5], [56], while the consistently lower expression levels of Bp Chr 2 and its condition response profiles more closely resemble profiles previously observed in plasmid pXO 1 in B. anthracis and pSymB in S. meliloti , respectively [57], [58]. Comparison of our gene expression data to previously published proteomic studies also revealed that there is a positive but modest correlation between transcript and protein data, as has been reported for other prokaryotes [46], [59][61] (Figure S8). However, to our best knowledge, this is the first formal report demonstrating the distinct transcriptional landscapes of multi-chromosomal bacteria, and suggests very different evolutionary origins for the two Bp chromosomes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, when compared against other prokaryotic transcriptome studies, the transcriptional landscape of Bp Chr 1 bears high resemblance to other single chromosomal microbes E. coli , L. monocytogenes and B. subtilis [4], [5], [56], while the consistently lower expression levels of Bp Chr 2 and its condition response profiles more closely resemble profiles previously observed in plasmid pXO 1 in B. anthracis and pSymB in S. meliloti , respectively [57], [58]. Comparison of our gene expression data to previously published proteomic studies also revealed that there is a positive but modest correlation between transcript and protein data, as has been reported for other prokaryotes [46], [59][61] (Figure S8). However, to our best knowledge, this is the first formal report demonstrating the distinct transcriptional landscapes of multi-chromosomal bacteria, and suggests very different evolutionary origins for the two Bp chromosomes.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, previous analysis of these novel genes has also shown that 46% are associated with other proteins in the COG, KEGG, STRING and NR databases, and high-confidence ribosome binding sites have also been identified in 60% of these novel genes [13]. Moreover, while several of these novel genes have short lengths (<500 bp), recent proteomic studies have confirmed the bona-fide expression of many short-length Bp genes [46], and in one study a newly identified short-length Burkholderia gene of 74 amino acids was experimentally demonstrated to regulate contact dependent growth inhibition [47]. Expression of short-length genes has also been confirmed in other bacterial species, such as MgtR in Salmonella (30 amino acids) [48], Sda in Bacillus subtilis (46 a.a.) [49], [50], YccB, YncL, YohP and IlvX in Escherichia coli (<50 a.a.) [51].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A B. pseudomallei protein reference map was previously created by the present authors ; this detected 282 protein spots on the 2D‐gels. In this study, the accuracy of protein identification was further improved by using more stringent criteria than previously employed (see Materials and Methods Section for more details).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, 2 immunogens (BPSS1904 and BPSS0897) that have been previously identified to be involved in bacterial adaptation processes and BURPS1710b_0454 is predicted to regulate cell envelope biogenesis. BPSS1904 was reported to play an essential role in the survival of B. pseudomallei during the early stationary phase of growth 35 whereas BPSS0897 was coexpressed with T3SS-associated genes in response to salt stress 36. However, the relative importance of these remain largely unknown, and therefore it would be valuable to further investigate in vivo or in vitro models that could give insights into B. pseudomallei virulence.…”
Section: Discussionmentioning
confidence: 99%